Aislamiento de microorganismos para la solución de problemas en el reservorio de aguas residuales, barrio 10 de Agosto, cantón Pujilí, provincia de Cotopaxi, periodo 2014 - 2015 - Izurieta Chicaiza, Diana Karolina (2015)
This research was conducted in wastewater reservoir of 10 de Agosto Neighborhood in Pujilí Canton, Cotopaxi Province, with the aim of solving pollution problems in the water usage for their crops and odor generated. It was identified and isolated microorganisms in the reservoir, resulting 30 cfu/100 ml Escherichia coli and 68 cfu/100 of Pseudomonas aeruginosa. The researcher proceeded to perform three trials: three contained 50 L of wastewater, the first was inoculated with 5ml of Escherichia coli, the second with 5ml of Pseudomonas aeruginosa and the third a mixture of the two bacteria that will be known as cocktail. As a result of the investigation the researcher found that Escherichia coli reduced contamination into oils and fats in 23.07%, Total Coliform in 97.08% and Total Nitrogen in 69.11%. Regarding to Pseudomonas aeruginosa in oils and fats it was reduced the pollution by 23.07%, Total Coliform in 97.16% and Total Nitrogen in 75.25%. With cocktail in oils and fats it was reducted the pollution by 23.07%, Total Coliform in 89.25% and Total Nitrogen in 72.18%....